2012
DOI: 10.1007/s00701-012-1307-3
|View full text |Cite
|
Sign up to set email alerts
|

Vascular compression of the cochlear nerve and tinnitus: a pathophysiological investigation

Abstract: Preoperatively, there is a marginal significant difference between the ipsi- and contralateral IPL III-V, which disappears postoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The tinnitus can be perceived unilaterally, bilaterally or holocranially. In bilateral tinnitus it can be perceived as one sound, or it can be perceived as two different sounds in the two ears, all likely to be associated with a different pathophysiology (De Ridder et al, 2007b;De Ridder et al, 2012b) and involving different brain areas (Vanneste et al, 2011a;Vanneste et al, 2011d). There are gender differences in the emotional aspects of tinnitus: in men and women with the same tinnitus intensity, the same tinnitus type and the same amount of distress, there are still differences in mood associated with differences in brain activation .…”
Section: Introductionmentioning
confidence: 99%
“…The tinnitus can be perceived unilaterally, bilaterally or holocranially. In bilateral tinnitus it can be perceived as one sound, or it can be perceived as two different sounds in the two ears, all likely to be associated with a different pathophysiology (De Ridder et al, 2007b;De Ridder et al, 2012b) and involving different brain areas (Vanneste et al, 2011a;Vanneste et al, 2011d). There are gender differences in the emotional aspects of tinnitus: in men and women with the same tinnitus intensity, the same tinnitus type and the same amount of distress, there are still differences in mood associated with differences in brain activation .…”
Section: Introductionmentioning
confidence: 99%
“…Microvascular compression of CNVIII has been proposed as a pathophysiological mechanism for tinnitus, with MVD of CNVIII potentially serving as a curative treatment [ 20 , 26 ]. One study showed that patients with both HFS and tinnitus had a neurovascular conflict of both CNVII and CNVIII, while this was less present in HFS patients without tinnitus.…”
Section: Discussionmentioning
confidence: 99%
“…As part of an auditory evaluation, each participant had a pure tone audiometry (PTA); when VP was suspected, auditory-evoked brainstem responses (ABR) were performed. According to Moller's criteria [21,22], compression on the CVN induces a slowing of signal transmission by the respective auditory nerve fibers, and the CVN involvement was suspected as soon as the I-III interpeak latency (IPL) was prolonged more than 2.3 ms on the affected side.…”
Section: Audio-vestibular Assessmentmentioning
confidence: 99%